2016
DOI: 10.1002/adom.201600219
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Characteristics of Noble Metal Nanoparticle–Molybdenum Disulfide Heterostructures

Abstract: near-fi elds and optical absorption [29][30][31] to improve light emission from MoS 2 despite plasmon-phonon coupling, [ 32 ] hot electron transport, [ 33 ] and recombination limitations. Gold (Au) nanoparticle-induced electric fi elds were reported to increase photoluminescence (PL) of MoS 2 1.7-to 2-fold [ 16,34 ] and tungsten disulfi de (WS 2 ) 10-fold. [ 35 ] In the latter, plasmon-exciton coupling had been maximized. Quenching of PL from MoS 2 by p-type doping was reported to result from smaller MoS 2 ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…15,16 This challenge has motivated intense research efforts focusing on enhancing light absorption by metallic particle sensitization and the resulting exciton-plasmon interactions. [17][18][19][20][21] Excitation of many types of metal particles in the visible or ultraviolet (UV) frequency range stimulates collective motions of electrons, known as surface plasmons, that exhibit wave-like densities extending beyond the material surface. Such coherent oscillations of conduction band electrons induced by an electromagnetic field give rise to strong absorption and scattering resonances, 22 driving charge separation at metal-semiconductor interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 This challenge has motivated intense research efforts focusing on enhancing light absorption by metallic particle sensitization and the resulting exciton-plasmon interactions. [17][18][19][20][21] Excitation of many types of metal particles in the visible or ultraviolet (UV) frequency range stimulates collective motions of electrons, known as surface plasmons, that exhibit wave-like densities extending beyond the material surface. Such coherent oscillations of conduction band electrons induced by an electromagnetic field give rise to strong absorption and scattering resonances, 22 driving charge separation at metal-semiconductor interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The advantageous properties of localized plasmon resonances have motivated many recent experiments focusing on the fabrication and characterization of various semiconductors sensitized with plasmonic particles, and showing promising photovoltaic and photocatalytic properties. [16][17][18][19][20][21] Shi and co-workers demonstrated that monolayer MoS 2 sensitized with gold nano-antennas exhibits a significantly enhanced photoresponse at the wavelength of the localized surface plasmon resonance. 20 Chen and co-workers reported that plasmonic-MoS 2 hybrids dramatically…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] As a result, Au 0 is produced and nucleates to form Au nanoparticles (AuNPs). Such TMD-Au hybrids are interesting for a number of applications ranging from rechargeable batteries, 27 to biosensing, 29,30 optoelectronics, [31][32][33] and catalysis. [34][35][36] Finally, as in any material, defects largely control the properties of the 2D nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of optoelectronic processes in nanoantenna-TMD heterostructures has to date focused on linear optical operations, where polarization, , responds linearly to the excitation field at frequency ω according to (1) . As examples, far-field optical absorption and scattering activity, 1 10-1000x enhanced TMD absorption/emission, 2 photoluminescence (PL) quenching, 3 and 11 to 38% efficient plasmonic hot electron transport 4,5 have been reported. Extraordinary second harmonic generation (SHG) and frequency mixing has been measured from twodimensional (2D) TMD arising from the second-order nonlinear contribution to that scales with 2 according to their large (2) .…”
Section: Introductionmentioning
confidence: 99%